Efektivitasekstrak Daun Afrika (Vernonia amygdalina Del) Sebagai Liquid Electric Untuk Membunuh Nyamuk Aedes Aegypti Tahun 2019 - alfin nadifatu zahroh; winarko winarko; nur haidah (Jurnal Penelitian Kesehatan SUARA FORIKES, 2020)
Aedes Aegypti is a vector carrying dangue virus. The use of chemical insecticides continuously can cause resistance to mosquitoes and pollute the environment. Another alternative can be used vegetable insecticide which is derived from African leaf plants. Phytochemical results of African leaves contain 68% alkaloids, 3.89% saponins, 2.16% terpenoids and 2.32% flavonoids. The purpose of this study was to determine the effectiveness of African leaf extract as a liquid electric to kill Aedes Aegypti mosquitoes. This study uses true experiments with a post test only control group design with a concentration of 30%, 35%, 40%, 45%, 50%, control and 4 replications. The number of mosquitoes used is 600 birds. Data were analyzed using the kruskal waills test. The results showed p